Recruitment and retention strategies for an urban adolescent study: Lessons learned from a multi‐center study of community‐based asthma self‐management intervention for adolescents. (26th March 2018) - Grape, Annette; Rhee, Hyekyun; Wicks, Mona; Tumiel‐Berhalter, Laurene; Sloand, Elizabeth
ABSTRACT: Intervention studies with urban adolescents and families affected by asthma are critical to improving the disproportionate morbidity in this population. Community‐based recruitment and retention strategies in a multi‐site longitudinal project evaluating an asthma self‐management intervention for adolescents are presented. Successful recruitment strategies depended on the geographic and cultural characteristics of each study site. Partnering with providers and groups known to the target population and in‐person contact with target population were found effective. Flexibility accommodating modified and new approaches, securing multiple contacts and repeating mailings as well as capitalizing on the benefits of subject payment was critical to achieving long‐term subject engagement of 85% in the study. Ongoing monitoring and adjustment of recruitment and retention strategies is recommended.